An Analysis of Employee Job Satisfaction at Rangpur Community Dental Medical College and Hospital: Key Factors and Organizational Impact - Uddin, Shamim (Magenta Journal De Healthymedi, 2024)
This study investigates employee job satisfaction at Rangpur Community Dental Medical College and Hospital, focusing on various domains influencing job satisfaction, including compensation, working conditions, interpersonal relations, and career development. The research employs a descriptive and quantitative methodology, collecting data from 90 employees using structured surveys and the Job Satisfaction Survey (JSS) scale. Results show that employees generally express moderate satisfaction, with significant variation across different job aspects. While interpersonal relations and cooperation are highly rated, indicating a positive work culture, dissatisfaction is notable in financial benefits, working conditions, and organizational facilities. Career development opportunities and human resource practices are also areas of concern. The findings highlight a need for the institution to address issues related to job benefits, professional growth, and recruitment processes. Improving these areas could enhance overall employee satisfaction and performance, leading to better outcomes for the hospital.